2024
DOI: 10.3390/cancers16111981
|View full text |Cite
|
Sign up to set email alerts
|

Early Breast Cancer Risk Assessment: Integrating Histopathology with Artificial Intelligence

Mariia Ivanova,
Carlo Pescia,
Dario Trapani
et al.

Abstract: Effective risk assessment in early breast cancer is essential for informed clinical decision-making, yet consensus on defining risk categories remains challenging. This paper explores evolving approaches in risk stratification, encompassing histopathological, immunohistochemical, and molecular biomarkers alongside cutting-edge artificial intelligence (AI) techniques. Leveraging machine learning, deep learning, and convolutional neural networks, AI is reshaping predictive algorithms for recurrence risk, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…Numerous studies have highlighted the efficacy of deep learning models in extracting critical information from routine pathological images, offering valuable clinical insights [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For instance, deep learning has been utilized for quantitative image analysis to forecast disease progression patterns, prognoses, and other clinical outcomes [ 27 , 28 , 29 , 30 , 31 ]. Despite these advancements, there remains a paucity of study specifically addressing AI-based STAS prediction using histopathological images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have highlighted the efficacy of deep learning models in extracting critical information from routine pathological images, offering valuable clinical insights [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For instance, deep learning has been utilized for quantitative image analysis to forecast disease progression patterns, prognoses, and other clinical outcomes [ 27 , 28 , 29 , 30 , 31 ]. Despite these advancements, there remains a paucity of study specifically addressing AI-based STAS prediction using histopathological images.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, deep learning approaches have shown promise in capturing intricate features within images more effectively. By employing end-to-end training, these methods enhance predictive capabilities and provide more accurate prognostic information [ 27 , 28 , 29 , 30 , 31 ]. For example, recent studies have demonstrated the application of deep learning models to various medical imaging tasks, achieving high performance metrics.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with EBC, precisely estimating the possibility of local or distant recurrence is of vital importance for assessing the risk–benefit degree of systemic therapies [ 5 , 6 ]. In particular, to guide the selection and de-escalation of adjuvant therapy, there is a need for diagnostic algorithms that enhance the information obtained from histological criteria by integrating them with molecular data [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%